An Unexpected Pathway to Enantiomerization of Hemithioketals in Toluene Involving a Dimeric Transition State: A Combined Experimental and Computational Study. Issue 20 (2nd June 2015) - Bottoni, Andrea; Calvaresi, Matteo; Cosimelli, Barbara; Mazzanti, Andrea; Rambaldi, Mirella; Spinelli, Domenico
Abstract: 5‐Alkyl‐8‐aryl‐8‐hydroxy‐8 H ‐[1, 2, 4]oxadiazolo[3, 4‐ c ][1, 4]thiazin‐3‐ones (1 ) and their thioketals (2 ) represent interesting hits as LTTC blockers as well as inhibitors of MDR1 activity. Compounds1 contain an unstable chiral centre which can give rise to an enantiomerization process, because of the possible equilibrium with the open‐chain forms4 . We have carried out a combined experimental‐computational study on the1 /4 equilibrium in toluene by using the 8‐(4‐bromophenyl)‐5‐ethyl‐8‐hydroxy‐8 H ‐[1, 2, 4]oxadiazolo[3, 4‐ c ][1, 4]thiazin‐3‐one (1a ), containing two diastereotopic hydrogen atoms. 1 H‐NMR techniques have allowed to calculate the relevant energy barriers for the enantiomerization process (ca. 20 kcal mol –1 ). QM computations have individuated a transition state for a concerted asynchronous process occurring on a dimer of1a with an activation barrier (ca. 23 kcal mol –1 ) in rather good agreement with the 1 H‐NMR experimental value, thus showing how a spontaneous mutarotation process could occur in non‐polar aprotic solvent. Abstract : NMR and DFT calculations showed how a spontaneous enantiomerization of hemithioketals occurring in toluene involves a dimeric transition state.